The Contribution of the Halal Tourism Sector to East Java's Economic Growth - Nizar, Muhammad; Ratnasari, Ririn Tri; Usman, Indrianawati (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study aims to analyze the impact of halal tourism on the economy of East Java, Indonesia. This study uses a qualitative approach. The findings show that the halal tourism industry has a positive effect on the culinary, hospitality, and transportation sectors, as well as creating new jobs. East Java's diverse tourist destinations, government support, and public awareness of the importance of sharia tourism have contributed to the growth of the halal tourism industry. However, challenges such as infrastructure and facilities, the quality of halal tourism services need to be overcome. The research implications suggest that the government and tourism industry players must intensify their efforts to meet the demands of Muslim tourists by increasing the quality and quantity of facilities such as halal hotels and restaurants, providing information and services that are easily accessible to tourists, and increasing training and certification of tourism industry players. The study concluded that the progress of halal tourism in East Java could have a wider positive impact. The originality of the research lies in the local context of East Java, which can yield different results. Additionally, East Java has the second-best economic growth in Indonesia.